2012
DOI: 10.1089/jamp.2011.0891
|View full text |Cite
|
Sign up to set email alerts
|

ProAir® HFA Delivers Warmer, Lower-Impact, Longer-Duration Plumes Containing Higher Fine Particle Dose Than Ventolin® HFA

Abstract: The ProAir(®) HFA delivers a warmer, lower-impact, and longer-lasting plume compared with Ventolin(®) HFA, which may provide a more consistent, comfortable experience for patients using a pMDI. ProAir(®) HFA produces higher fine particle dose than Ventolin(®) HFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…The aerosol characteristics of the pMDI alone of Ventolin and ProAir are similar to those reported by McCabe et al 9 They reported an MMAD/GSD/fine-particle dose (calculated as mass for percentage Ͻ 5 m) for Ventolin alone of 2.4 m/2.0/26 g, compared with our findings of 2.39 m/1.41/29.3 g. Similarly, they reported MMAD/GSD/fine-particle dose for ProAir alone of 2.3 m/1.6/53 g, and we measured 2.21 m/1.43/42.9 g.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The aerosol characteristics of the pMDI alone of Ventolin and ProAir are similar to those reported by McCabe et al 9 They reported an MMAD/GSD/fine-particle dose (calculated as mass for percentage Ͻ 5 m) for Ventolin alone of 2.4 m/2.0/26 g, compared with our findings of 2.39 m/1.41/29.3 g. Similarly, they reported MMAD/GSD/fine-particle dose for ProAir alone of 2.3 m/1.6/53 g, and we measured 2.21 m/1.43/42.9 g.…”
Section: Discussionsupporting
confidence: 86%
“…We speculate that the difference in magnitude seen between ProAir and the others is because its aerosol velocity is slower than the others. 7,9 Hautman et al 7 limited the particle size distribution analysis to fine-particle mass. Our study provides a more complete description of the aerosols and also introduces the effect of delay between actuation and measurement as novel data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FPF for mannitol and CSLA microparticles was determined to be 49% and 46%, respectively, which is excellent, falling within those of commercial HFA-based pMDIs for small-molecule therapeutics (30–55% on average) 65,71 even though no optimization was attempted in our case. It is worth noticing that FPFs for both formulations were not significantly different ( n = 2, One-Way ANOVA followed by Tukey’s posthoc test, p value <0.05).…”
Section: Resultsmentioning
confidence: 48%
“…The median mass aerodynamic diameter of the aerosols generated ranges from 2.3 to 3.1 m. The jet and vibrating mesh nebulizers have label specifications of 2.7 and 3.1 m, respectively, whereas the pMDI has a reported median mass aerodynamic diameter of 2.3 m. 19 The jet and vibrating mesh nebulizers were filled with albuterol sulfate (2.5 mg/3 mL, Nephron Pharmaceuticals, Orlando, Florida). The jet nebulizer was operated with oxygen at 8 L/min using a calibrated flow meter.…”
Section: Types and Operation Of Aerosol Devicesmentioning
confidence: 99%